Sport officiating recruitment, development, and retention - Lori A. Livingston; Susan L. Forbes; Nicky Pearson; Tony Camacho; Nick Wattie; Paul Varian (Bern Open Publishing, 2017)
The purpose of this article is to report on the outcome of a two-day consensus-building exercise amongst sport scientists and sport practitioners interested in the recruitment, development, and retention of sport officials.  Twenty participants including volunteers and paid employees affiliated with nine Ontario-based sport organizations, university researchers, and provincial government policy makers participated.  A consensus statement regarding this aspect of sport officiating and, more specifically, "What do we know?", "What don't we know?", and "Where does the research need to go from here?" is presented.  A willingness to consider and embrace these ideas may be critical in moving sport officiating from being an understudied and undervalued segment of the sport system to receiving the attention and respect it deserves going forward.